Colored aluminates pigments obtained from metallic aluminum waste, an opportunity in the circular economy - Dienifer F.L. Horsth (Elsevier, 2021)
In order to contribute to sustainability and follow the goals of the circular economy, colored aluminates were prepared using metallic aluminum (discarded tin seal) as a precursor for application as ecofriendly synthetic inorganic pigments. To obtain colored pigments, aliquots containing aluminum in solution (by acid digestion) were doped (10%, m/m) with Cr, Mn, Fe, Co, Ni chloride salts precipitated by pH control, followed by either drying at 70 °C or calcination at 1000 °C. The pigments were characterized by X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, Raman and electronic spectroscopy. The data analysis indicates the transformation of the alumina phase (η-Al2O3) into aluminates by insertion of coloring ions, with a low degree of crystallinity (<41%), and average crystallite size less than 50 nm, i.e., nanoparticles. The composition was estimated as aluminates [Mx(Al2O4)1-x] for x = 0.21–0.43, ie, corresponding to a range between 10 and 27% chromophore metal. Colorimetric measurements were performed according to the CIEL*a*b* colorimetry system. Pigments are mostly in the quadrant (+a and +b) and can be classified as hot colors, which remain when dispersed in paint. The use of colored aluminates from recycled metallic aluminum as synthetic inorganic pigments was shown to be feasible.